IMPLEMENTASI KURIKULUM MERDEKA BERBASIS PENDIDIKAN KARAKTER DI RA NURUL ROHMAH BEKASI - Yuliwati; Wahyuni Nadar; Mareta Bayani (Al Hanin, 2025)
This research aims to obtain information about the implementation of the Merdeka Curriculum based on Character Education and the inhibiting and supporting factors at the Raudhatul Athfal (RA) Nurul Rohmah unit in Bekasi City. This type of research is qualitative research with a descriptive narrative approach. Data collection using interview techniques, direct observation, and document collection. The informants in this study consisted of 6 people, namely the Principal and 5 educators. Data analysis used the Miles and Huberman model, and data validity was ensured through triangulation. Data analysis using the Miles and Huberman model, with data validity assessed through triangulation. The research results can be described as follows: RA Nurul Rohmah has implemented the character-based Independent Curriculum through 3 stages, namely (1) Planning; (2) Implementation; and (3) Evaluation. In the planning stage, the Principal together with the teachers prepares the Operational Curriculum of Educational Units (KOSP) as well as teaching modules and the Project Module for Strengthening Pancasila Student Profiles (P5). In the implementation stage, through intrakurricular learning activities and learning with the P5 approach. In the final stage, evaluation is conducted on the implemented learning, resulting in a culture of reflection accompanied by guidance and professional development from the head of the school to the teachers. The inhibiting factors identified are the teachers' experience and the lack of references on curriculum development and evaluation itself. Supporting factors are the management of the school principal and the digital learning platform based on Android provided by the Government.